Growth and Biomasr Production of Selected Fuel Wood Tree Species in Mid Hill of Western Himalaya in India - , Ooficuaku; Bin, D. (Indian Forester, 2011)
a study was conducted to evaluate effect of spacing, fertilizer and irrigation on growth and biomass production of some selected fuel wood tree species in palampur located in mid hill of western himalaya, India. Two experiments were conducted separately underrain fed and irrigated conditions. Twelve fast growing fuel-wood tree species were plated in september 1993. Various physiological parameters including conductance, water potential, photosynthesis rate etc. , were measured regularly. Data collected during 3 years of the studies showed that Eucatyptus hybrid was unaffected in the adversities of the environment whereas Salixtetrasperma was the most sensitive crop. Different doses of N, P and K did not affect the observed physiological parameters; however, investigation provided information on crop-specific optimal doses of N, P and K on plant performance. The paper dissects various aspects of plant performance in relation to water potential, environmental variables and fertilizer doses for optimal plant productivity. Eucalyptus, Melia azedarach, Grevillea robusta and Toona ciliata exhibited lower water potential during lean period especially in the months of June, September and October. The survial rate of all the species were found above 90% except Salixtetrasperma, which showed 75% survivulrute.